Together divided–divided together: Intersections of symbolic boundaries in the context of ex-Yugoslavian immigrant communities in Vienna. (December 2020) - Mijić, Ana
The inspiration for the following research arose from an identified ambivalence regarding the question of how relevant ethnic belonging – being Bosniak, being Croat, being Serb – is in everyday life of ex-Yugoslavian Viennese people. A qualitative analysis of narrative interviews as well as participant observations on Vienna's Ottakringer Straße, a neighbourhood highly frequented by immigrants from the former Yugoslavia and their descendants, indicates that ethnicity indeed matters, particularly when it comes to questions of partner choice. The research, however, also reveals that there are further, intersecting boundaries encompassing or dividing the 'ex-Yugoslavian community': In light of being othered by the Austrian majority society and defined as 'incomplete self' Maria Todorova, i.e. as representatives of a sphere between the own and the foreign, educationally alienated young adults across ethnic boundaries notably celebrate the culture of 'turbo folk' on Ottakringer Straße – a lifestyle that emphasises their own 'glamour and passion' as opposed to Austrian 'bleakness'. Therewith they reinforce the image of the 'Balkan Other'. Simultaneously, 'ex-Yugoslavian' Viennese with higher education levels exhibit a substantial need to not only distinguish themselves from turbo folk and (night-)life on Ottakringer Straße, but also from the image of the 'Balkan Other'. By emphasising their own 'more sophisticated' taste, they express their social position in terms of a specific lifestyle and set themselves apart from the 'uneducated and common immigrants'. Hence, the analysis shows that, with regard to the 'ex-Yugoslavian communities' in Vienna, different symbolic boundaries are at work: the ethnic boundaries – (re-)constructed and (re-)enforced by the wars in the former Yugoslavia – the 'Balkanised' symbolic boundaries between ex-Yugoslavian minorities and the Austrian majority as well as the milieu-specific symbolic boundaries within the community itself.